2016
DOI: 10.5658/wood.2016.44.5.776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physico-mechanical Properties and Durability of Larix kaempferi Wood Heat-treated by Superheated Steam

Abstract: In this study, green Larix kaempferi lumber was heat-treated by using superheated steam (SHS) at a pilot scale and then various physico-mechanical properties of the heat-treated wood were evaluated and compared with the properties of conventional hot air (HA) heat-treated wood. Decay resistance of brown rot fungi and compressive strength parallel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 7 publications
0
17
0
7
Order By: Relevance
“…At the beginning of the combined treatment, the temperature and pressure of the SHS and temperature of the lumber increased rapidly. When the temperature and pressure of the SHS reached the target temperature (250°C) and the target pressure (0.5 MPa), the temperature of the lumber reached the saturation temperature (151.8°C) of steam at 0.5 MPa and was maintained for 3 h. Park et al [19] reported that the wood specimen was oven-dried when the temperature of the wood specimen was maintained constantly and re-increased. In other words, the water in the wood was completely removed for the duration of the constant temperature, and the temperature of the wood was re-increased by the heat energy which had been used to remove the water in the wood was used to heat the wood.…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning of the combined treatment, the temperature and pressure of the SHS and temperature of the lumber increased rapidly. When the temperature and pressure of the SHS reached the target temperature (250°C) and the target pressure (0.5 MPa), the temperature of the lumber reached the saturation temperature (151.8°C) of steam at 0.5 MPa and was maintained for 3 h. Park et al [19] reported that the wood specimen was oven-dried when the temperature of the wood specimen was maintained constantly and re-increased. In other words, the water in the wood was completely removed for the duration of the constant temperature, and the temperature of the wood was re-increased by the heat energy which had been used to remove the water in the wood was used to heat the wood.…”
Section: Resultsmentioning
confidence: 99%
“…Heated at a high temperature (160~260℃), the principal components that consist of the cell walls of wood (cellulose, hemicellulose, and lignin, etc.) experience chemical changes like thermal hydrolysis process, which results in changing the physical-dynamic as well as weatherproof performance (Militz, 2002;Park et al, 2016). Various research on wood heat treatment as an environmental-friendly preservative and insect-proof process since the early 2000s has been conducted mainly in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been research on the heat treatment with superheated steam on wood (Park et al, 2012;Park et al, 2014;Park et al, 2016;Han et al, 2017;Park et al, 2017a;2017b). Superheated steam is a steam of which temperature is over the boiling temperature and is used to dry not only wood, but food or sewage sludge (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations